The Benefits of Digital Financial Applications on Improving the Company's Accounting Performance - Leon, Hengky; Heru, Mochammad; Ricky, Ricky; Cakranegara, Pandu Adi; Setiawan, Iwan (Budapest International Research and Critics University, 2022)
Running a business is a job that requires high efficiency and productivity. This productivity can also come from the company's bookkeeping or accounting work efficiency. The use of digital technology is one of the goals to gain efficiency towards profitable and sustainable company productivity. For this reason, we have carried out this study intending to get the benefits and benefits of using digital technology to ease the company's accounting work. In order to be able to answer the questions and hypotheses of this study, we have conducted a series of data searches on accounting and technology databases from several international publications. The data we collect we examine using a phenomenological approach to search for as much data as possible to get plant parts that can answer this royal question. The process has involved data coding, data interpretation, and critical evaluation in obtaining relevant answers to questions. Based on the study and discussion of the data, we can conclude that several benefits and advantages are obtained when companies, especially the accounting department, can utilize digital applications in handling the company's financial work tasks, all of which are useful for improving the company's accounting performance. Hopefully, this new finding will be a significant input for efforts to develop a similar study in digital financial applications towards improving the accounting performance of both public and private companies.Â